Application of the CARE guideline as reporting standard in the Therapeutic Radiology and Oncology - Office, Editorial (Therapeutic Radiology and Oncology, 2019)
The Therapeutic Radiology and Oncology welcomes case reports which are supposed to report new observations of diseases, clinical findings or novel/unique treatment outcomes relevant to practitioners in the fields of medicine.